Rapid and sensitive quantification of efavirenz in rat plasma using HPLC-MS/MS method - Leandro Tasso; Thamyrys Barreto Argenta; Beatriz Ferreira de Carvalho Patricio; Helvécio Vinícius Antunes Rocha (Drug Analytical Research, 2024)
This article aims to analyze the development of a rapid and sensitive HPLC–MS/MS method for quantification of efavirenz in rat plasma. The developed method included a liquid-liquid extraction process with methyl-tert-butyl ether solution, where hydrochlorothiazide was used as internal standard. The analyte was separated on an ACE Phenyl C18 column and eluted by a system consisting of mobile phase A (0.2% acetic acid) and mobile phase B (acetonitrile) at a proportion of 35:65 (v/v), pumped with a flow rate of 1.0 mL min-1 (run time < 4 min). Mass spectrometric detection was performed on a triple quadrupole instrument using multiple reaction monitoring. The electrospray ionization source was performed in negative ion mode. The precursor/product ion pairs monitored were m/z 313.644→68.800 and m/z 295.541→268.700 for efavirenz and internal standard, respectively. The limit of quantification was 10.0 ng mL-1 and calibration curves were linear over 10.0–1,500 ng mL-1. Intra-day and inter-day precision at three levels were 1.80–10.49% and 4.72–10.28%, respectively. Accuracy ranged between 93.54% and 105.73%. Finally, the described method was applied to rats administered with efavirenz, demonstrating the suitability for quantification of efavirenz in a pharmacokinetic study. Therefore, it can be used in normal, hemolyzed or lipemic samples for efavirenz quantification.